TURNOVER INTENTION - Akça, Yaşar; Karagüzel, Aynur; Akça, Yaşar (Bartın Üniversitesi, 2023)
Manpower is the most important business resource of an enterprise. In order to achieve sustainable success in the global competitive environment, it is of great importance to protect and maintain this power. For a healthy organization, the willingness and perseverance of the employees towards the work enables them to move away from the intention to leave the job. Because happy employees do not look at the thought of leaving the job and can contribute more to the success of the organization they work for. The purpose of this conceptual article; It aims to summarize the basic information explaining the intention to leave the job and the factors affecting this intention of the human power, which is the lifeblood of the organizations. Since the intention to leave the job attracts great attention by both researchers and managers; It is thought that this article will benefit future researches and also managers.

İnsan gücü, işletmenin en önemli kaynaklarından birini oluşturmaktadır. Küresel rekabet ortamında sürdürülebilir başarı elde edebilmek için, bu gücün korunması ve devamının sağlanması büyük önem arz etmektedir. Sağlıklı bir örgüt için çalışanların işe karşı istekli olmaları ve işten ayrılma niyetinden uzaklaşmaları sağlanmalıdır. Çünkü mutlu çalışanlar, işten ayrılma düşüncesine sıcak bakmamakta ve çalıştıkları işletmenin başarılarına daha fazla katkı sunmaktadırlar. Bu makalenin amacı; insan kaynağının işletmeden ayrılma niyetini etkileyen faktörleri ortaya koymaktır. İşten ayrılma niyeti hem araştırmacılar hem de yöneticiler tarafından yoğun ilgi görmektedir. Dolayısıyla; gerçekleştirilen bu çalışmanın gelecekte yapılacak araştırmalara fayda sağlayacağı düşünülmektedir.
İşten Ayrılma Niyeti
Keywords: Business Administration; İşletme